2020
DOI: 10.1186/s12998-020-00327-4
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of cervicothoracic junction mobilization versus thoracic manipulation on the range of motion and pain in mechanical neck pain with cervicothoracic junction dysfunction: a pilot randomized controlled trial

Abstract: Background Cervicothoracic (CT) junction hypomobility has been proposed as a contributing factor for neck pain. However, there are limited studies that compared the effect of CT junction mobilization against an effective intervention in neck pain. Thoracic spine manipulation is a nonspecific intervention for neck pain where remote spinal segments are treated based on the concept of regional interdependence. The effectiveness of segment-specific spinal mobilization in the cervical spine has been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Somit steht auch der anatomische CTÜ mit wichtigen Strukturen in Verbindung. Aufgrund regionaler Interdependanz können Schmerzen im Zervikalbereich auch mit Manipulationen an der thorakalen Wirbelsäule gleichsam erfolgreich behandelt werden 22 . So wurde die Manipulation des CTÜ unterstützend zu lokaler Therapie bei Dysfunktionen des Temporomandibulargelenks erfolgreich eingesetzt 23 .…”
Section: Der Zervikothorakale üBergang (Ctü)unclassified
“…Somit steht auch der anatomische CTÜ mit wichtigen Strukturen in Verbindung. Aufgrund regionaler Interdependanz können Schmerzen im Zervikalbereich auch mit Manipulationen an der thorakalen Wirbelsäule gleichsam erfolgreich behandelt werden 22 . So wurde die Manipulation des CTÜ unterstützend zu lokaler Therapie bei Dysfunktionen des Temporomandibulargelenks erfolgreich eingesetzt 23 .…”
Section: Der Zervikothorakale üBergang (Ctü)unclassified
“…The most frequent active comparators used against SMT were other interventions commonly used for the management of NP, such as exercise or physical therapy modalities (43)(44)(45)(46)(47)(48)(49)(50). Additional studies compared the application of SM to that of mobilization techniques or examined the effect of different SM application sites (cervical vs. thoracic) (51)(52)(53)(54)(55)(56)(57)(58). However, these trials often measured short-term effects after short periods of care, which may not be as informative to clinical practice.…”
Section: Effectiveness Of Spinal Manipulative Therapy For Neck Painmentioning
confidence: 99%
“…Hence, mobilization is sometimes referred to as non-thrust SM (55,59). When directly comparing the application of SM to mobilization, several studies reported no significant differences in pain intensity, disability, range of motion or quality of life, although all outcomes improved significantly regardless of the intervention (41,51,54,(56)(57)(58). However, when comparing both interventions to a control (inactive treatment) group, neither was successful at reducing pain (41).…”
Section: Effectiveness Of Spinal Manipulation Compared To Mobilization For Neck Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Ganesh et al [20] reported a significant increase in the cervical mobility by applying Maitland mobilization to patients with cervical pain who complained of symptoms for less than 12 weeks. Meanwhile, Joshi et al [21] reported that in a patient complaining of pain at the junction of the cervical vertebrae and the vertebrae, Maitland mobilization was applied to the cervical vertebrae to significantly increase the mobility in cervical flexion and extension, as well as outward flexion and rotation.…”
Section: Introductionmentioning
confidence: 99%